Improving anion-exchange efficiency and spectrum stability of perovskite quantum dots via an Al3+ bonding-doping synergistic effect. Issue 12 (21st February 2023) - Yang, Linxiang; Shan, Qingsong; Zhang, Shuai; Zhou, Yihui; Li, Yan; Zou, Yousheng; Zeng, Haibo
Abstract : We report an Al 3+  bonding-doping synergistic strategy by anion exchange for stable deep-blue perovskite QD and QLED. The QD exhibits superior stability against moisture and electric field, the spectrum-stable QLED achieves an EQE of 1.38% at 463 nm. Abstract : Anion-exchange reactions are recognized as a vital and facile post-synthesis method to precisely manipulate the emission spectra of perovskite quantum dots (QDs). However, the anion-exchange process often induces adverse structural evolution and trap-mediated mechanisms, so mixed-halide perovskite QDs suffer inefficient anion exchange and poor spectra-stability issues, which limits access to high-quality primary color perovskite QDs for display applications. Here we report an Al 3+ bonding-doping synergistic strategy for manufacturing stable mixed Br/Cl deep-blue perovskite QDs. By doping Al 3+ into perovskite QDs, highly-efficient Cl − anion exchange and a large-range blue shift of the PL spectrum (∼62 nm with only 0.1 mmol of Cl feed) can be easily achieved. Notably, the Al 3+ -mediated deep-blue emission sample exhibits superior stability against moisture and electric fields. It also shows an elevated valence band maximum level. Based on the anion-exchanged QDs, a spectrum-stable deep-blue QLED with an EQE of 1.38% at 463 nm is achieved. Our findings demonstrate a feasible and promising strategy for developing high-performance deep-blue perovskite materials and optoelectronic devices.